Faktor Sosial Yang Mempengaruhi Pendapatan Pedagang Sayur Di Pasar Wonorejo Kecamatan Wonorejo Kabupaten Pasuruan - Nabila, Imroatun; Hidayati, Novi Itsna (Universitas Panca Marga, 2022)
Socio-economic factor is the position or position of a person in a community group which is determined by the type of economic activity carried out to obtain how much income. The level of income can also be influenced by socio-economic factors, if the socioeconomic status of an individual is low, the need for food is less or less so that it can reduce the income of a vegetable trader. The purpose of this study is to determine the level of income obtained from vegetable traders in the Wonorejo market and analyze the socio-economic factors that affect the income of vegetable traders in the Wonorejo market. The sample of this research is that consist of 32 people. The data used in this study include primary data and secondary data. The analytical method used is the income of vegetable traders and multiple linear regression. The results of this study are the income earned by vegetable traders in Wonorejo, which is 2,650,400 per month, this is because the higher the capital used, the higher the income earned by vegetable traders at the Wonorejo Market factors - factors that affect income, namely capital has a significant effect on income, while the variables of age of business experience, number of dependents, education level, have no significant effect on the income of vegetable traders in Wonorejo Market..Keywords: Socio-Economic Factor, vegetable traders, Income.